2011
DOI: 10.1093/alcalc/agr083
|View full text |Cite
|
Sign up to set email alerts
|

Is Controlled Drinking an Acceptable Goal in the Treatment of Alcohol Dependence? A Survey of French Alcohol Specialists

Abstract: Half of French alcohol specialists accept CD as a goal. Acceptance was associated with specialists' personal and professional characteristics. The criteria for success specialists use in their clinical practice differ from those they expect to be used in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 21 publications
4
28
0
1
Order By: Relevance
“…This finding further supports the clinical relevance of the once controversial treatment goal of reducing consumption in alcohol-dependent patients [28], a concept which in recent years has gained increased acceptance [6,29,30]. …”
Section: Discussionsupporting
confidence: 73%
“…This finding further supports the clinical relevance of the once controversial treatment goal of reducing consumption in alcohol-dependent patients [28], a concept which in recent years has gained increased acceptance [6,29,30]. …”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, it should be noted that the literature does not offer consensus on the operational definition of drinking goal (Luquiens et al, 2011). Instead, the authors categorized responses to the Commitment to Abstinence item based largely on clinical judgment and prior research using this measure.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that 78.1% of persons abusing alcohol or being dependent to alcohol are not seeking any kind of therapy (154,155). One of the reasons for avoiding therapy is that some people may want to reduce the amount of alcohol used but are not inclined towards total abstinence (156). To choose harm reduction as a treatment goal can be a important step that may lead to an internalization of consuming less alcohol, possibly leading towards total abstinence (157).…”
Section: Reduction Of Heavy Drinking (Harm Reduction)mentioning
confidence: 99%